Employer Branding and Job Application Intention: The Mediating Role of Corporate Reputation among Generation Z - Amilatusysyifa Izzatunnawa; Nanda Adhi Purusa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study investigates how the perception of corporations acts as a mediator connecting employer branding with applicants’ intentions to apply for jobs from the Gen Z demographic in Indonesia’s private banking sector. While the broader context refers to the Indonesian private banking industry, the empirical support identified in this study was drawn from Semarang, involving 120 Generation Z respondents who were either final-year students or recent graduates residing in the city. A quantitative design was conducted through a survey approach with purposive sampling, and data were acquired through web-based questionnaires. The evaluation was carried out employing the PLS-SEM method with SmartPLS version 4. 0. The findings indicate that employer branding significantly influences both the reputation of the company and the likelihood of application in a positive manner. Additionally, a company's reputation is strongly and positively linked to the intention to apply, serving as a bridge between employer branding and the desire to seek employment opportunities. The study highlights that employer branding, when managed effectively, enhances Generation Z’s application intention, operating both as a direct driver and via the mediating influence of corporate reputation. Practically, this implies private banks in Indonesia particularly those operating in Semarang should concentrate on advancing employer branding practices while upholding a strong corporate reputation to draw and involve talented candidates from Generation Z. This study provides a contribution to the academic field by highlighting empirical evidence collected in Semarang reflect the interaction between employer branding and corporate reputation in influencing job application behavior of Generation Z within the private banking sector.